Circulation environment in urban spaces for pedestrians with mobility constraints : a case study in Braga, Portugal - Rodrigues, Daniel Souto (2011)
Mobility is pointed as a key issue to urban planners and managers. In particular the case of pedestrians with mobility constraints implies considering specific parameters. The goal of the present work is to analyse factors that limit the circulation of people with mobility constraints and to map those conditions in central urban spaces. Taking into account only the physical characteristics of urban spaces, the assessment is performed in agreement with the standards specified in the Portuguese Law. A multi-criteria model was developed to evaluate the compliance of urban spaces with those standards. Its integration within a GIS platform was performed in order to implement a spatial analysis of the results. A case study was conducted in a central area of the city of Braga, Portugal. Maps showing levels of compliance with the standards were produced and the results were discussed.